Feasibility of the authority of will in the rights governing the personal status - Mohammad Babolhekami; Farhad Parvin (پژوهشهای حقوقی)
In recent years, the countries of the world have expanded this principle in personal and family matters; which has led to greater coordination of their legal system and reduced conflicts. The European Union is a pioneer in this field by approving the Rome 3 Convention and the Brussels Regulation. Iranian law has considered the principle of the sovereignty of the will only in contractual matters and has been silent about personal circumstances An important question raised in this article is why should this principle be used in personal situations? What are the conditions for using this principle? What is the scope of the law of choice? In response, we should state the hypothesis that increasing coordination and reducing conflicts between countries will strengthen legal stability and interests of individuals, which is one of the important results of using the principle of sovereignty of will.Individuals are only able to use the laws related to the subject (residence, citizenship and seat of the court) as the competent law. It is possible to use the law agreed by citizens in personal situations as long as it does not conflict with public order, good morals and human rights, otherwise the court should not implement it. Now, it seems that according to the benefits of this principle in personal situations, it is better that the legal system of Iran also uses it under certain conditions.